2021
DOI: 10.1007/s00330-020-07629-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between manual and artificial intelligence–based automatic positioning in CT imaging for COVID-19 patients

Abstract: Objective To analyze and compare the imaging workflow, radiation dose, and image quality for COVID-19 patients examined using either the conventional manual positioning (MP) method or an AI-based automatic positioning (AP) method. Materials and methods One hundred twenty-seven adult COVID-19 patients underwent chest CT scans on a CT scanner using the same scan protocol except with the manual positioning (MP group) for the initial scan and an AI-based autom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The distance of the patient centre to the gantry iso-centre is often measured on a single slice rather than on several slices or the whole stack [5,14]. For symmetric phantoms, this distance is usually identical throughout the image stack; however, for patients or anthropomorphic phantoms, the distance to the iso-centre varies along the z-axis.…”
Section: Discussionmentioning
confidence: 99%
“…The distance of the patient centre to the gantry iso-centre is often measured on a single slice rather than on several slices or the whole stack [5,14]. For symmetric phantoms, this distance is usually identical throughout the image stack; however, for patients or anthropomorphic phantoms, the distance to the iso-centre varies along the z-axis.…”
Section: Discussionmentioning
confidence: 99%
“…16 For CT, AI could assist imagers with dose optimization by automating patient positioning using the specific acquisition protocol. 17 In MRI, AI tools can detect and mitigate motion artifacts to improve image quality 18 ; accelerate acquisitions, leading to overall shorter examination times 19 ; and automate contouring for evaluation of ventricular volumes and ejection fraction. 20…”
Section: Value Definedmentioning
confidence: 99%
“…In both studies, significant improvement in patient centering was achieved, compared to manual positioning, with less extreme standard deviations from the ideal isocenter of the patients. More recently, a study by Gang et al, utilizing automated positioning, demonstrated a decrease of 16% in the dosage supplied to the patient, with a saving of 28% of the time [ 18 ].…”
Section: Ai In Image Acquisitionmentioning
confidence: 99%